Estrategia de entrenamiento y acompañamiento a usuarios para el Sistema de Información Hospitalaria XAVIA HIS. - Milán Cristo, Nadiezka; Ramírez Pérez, José Felipe; Vega Izaguirre, Leodan (Revista Cubana de Informática Médica)
End user training is one of the computer system deployment process stages. The technical changes depth impact on the organization and on employees when implementing a computer system sometimes is underestimated and the training service is not hired. This article describes a training and accompaniment strategy for users in the Hospital Information System XAVIA HIS implementation process. Main results are related to the actions, methods and techniques definition that allow planning and executing the training and accompaniment services with greater efficiency of the activities carried out. Also, the paper present the basic training programs for computer specialists, health technicians and professionals.